Experimental studies on the mechanical behavior of fouled ballast using large-scale testing - Venuja, S.; Navaratnarajah, S.K. (University of Toronto, Canada., 2023)
Rail transportation is a resource-efficient mode of transportation that provides economic benefits, higher safety, and lessens travel time. Ballasted rail tracks are the conventional and popular rail tracks all around the world. The ballast layer, which consists of highly angular granular particles with sizes ranging from 15 to 65 mm, is designated as the principal load- bearing structure in a ballasted track foundation. The void ratio of the ballast layer is high as it consists of various sizes of angular particles, facilitating water to drain out efficiently from the track. Nevertheless, ballast is fouled and degraded with time due to particle breakage and foreign material intrusion. This deterioration of the ballast layer significantly affects the performance and longevity of the rail track while impeding track drainage.